2014
DOI: 10.1634/theoncologist.2014-0195
|View full text |Cite
|
Sign up to set email alerts
|

Gene Status in HER2 Equivocal Breast Carcinomas: Impact of Distinct Recommendations and Contribution of a Polymerase Chain Reaction-Based Method

Abstract: Background. The primaryobjectives of this studyon carcinomas with equivocal HER2 expression were to assess the impact of distinct recommendations with regard to identifying patients eligible for anti-HER2 agents by fluorescence in situ hybridization (FISH) and to elucidate whether multiplex ligationdependent probe amplification (MLPA) may be of support in assessing HER2 gene status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
7
32
0
Order By: Relevance
“…A recent study also showed that the percentage of Her-2 D-FISH equivocal cases was as high as 9.4% according to the ASCO/CAP 2013 guidelines [16], similar to our results. Several other studies also demonstarted a significant increase in the D-FISH equivocal cases after the ASCO/CAP 2013 guideline update [12,14,15,17,18]. In addition, our assay revealed the interpretation of D-FISH equivocal results with good reproducibility.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A recent study also showed that the percentage of Her-2 D-FISH equivocal cases was as high as 9.4% according to the ASCO/CAP 2013 guidelines [16], similar to our results. Several other studies also demonstarted a significant increase in the D-FISH equivocal cases after the ASCO/CAP 2013 guideline update [12,14,15,17,18]. In addition, our assay revealed the interpretation of D-FISH equivocal results with good reproducibility.…”
Section: Discussionsupporting
confidence: 63%
“…Multiplex ligation-dependent probe amplification (MLPA) may be of support in reassessing Her-2 gene status of D-FISH equivocal cases. A recent report suggested that MLPA could rule out Her-2 amplification in 75% of ISH-evaluated Her-2-equivocal carcinomas [14]. Her-2 mRNA expression analysis by quantitative reverse transcription-PCR (qRT-PCR) may also be of help to determine the status of Her-2 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, they reported an increase in equivocal cases when using the ASCO/CAP 2013 ISH algorithm (12.3%) compared with the ASCO/CAP 2007 ratio criterion (2.4%). 7 Additional evaluation of the data by Sapino et al 7 reveals that although only 2.4% of the 2007 cases were equivocal by ratio, 13.5% would have been equivocal by copy number alone using the 2013 guidelines or by the ❚Image 1❚ HER2 fluorescence in situ hybridization (FISH; dual-color PathVysion FISH assay) and immunohistochemical assessment of a representative equivocal breast carcinoma. A HER2 equivocal case from 2013 cohort demonstrates (A) HER2 (red signals) to CEP17 (green signals) ratio of 1.9 and HER2 copy number of 4.8 (DAPI counterstain; ×1,000) and (B) reflex HER2 immunohistochemistry (IHC) showing incomplete, weak to moderate membrane staining in more than 10% of tumor cells, scored as HER2 2+ (×40) (inset, IHC HER2 3+ control, ×40).…”
Section: Discussionmentioning
confidence: 99%
“…This is important, because previous studies have suggested that neoplasms with increased HER2 copy number respond to anti-HER2 treatment in a manner that is largely independent of Cep17 counts, even when HER2 copy number is in the equivocal range. 7,9,10,13 Furthermore, other studies, including that of Muller and colleagues, suggest a trend toward higher grade and higher Ki-67 counts among ISH equivocal cases when comparing cases identified by 2013 criteria with those defined by 2007 criteria. 7,9,14 The implication of these findings is that the equivocal group defined by 2013 criteria (unlike the 2007 defined cohort) may in fact be enriched in patients who may benefit from anti-HER2 or combination therapy in the adjuvant or neoadjuvant setting.…”
mentioning
confidence: 88%
“…7,9,10,13 Furthermore, other studies, including that of Muller and colleagues, suggest a trend toward higher grade and higher Ki-67 counts among ISH equivocal cases when comparing cases identified by 2013 criteria with those defined by 2007 criteria. 7,9,14 The implication of these findings is that the equivocal group defined by 2013 criteria (unlike the 2007 defined cohort) may in fact be enriched in patients who may benefit from anti-HER2 or combination therapy in the adjuvant or neoadjuvant setting. 5,7,15 And because the 2013 criteria also tend to shift a subset of 2007 defined ISH equivocal into the positive category, [5][6][7]9,15 the net result of increased ISH equivocal rates may in fact be an improvement in overall patient care.…”
mentioning
confidence: 88%